2019
DOI: 10.1111/1475-6765.12358
|View full text |Cite
|
Sign up to set email alerts
|

If I'll win it, I want it: The role of instrumental considerations in explaining public support for referendums

Abstract: Across established democracies, citizens express high levels of support for decision making via referendums. What drives these preferences remains yet unclear. In this article it is argued that, first, process preferences are less stable than previously assumed but vary substantially across policy proposals. Second, it is suggested that instrumental considerations play an important role in shaping citizens' preferences for referendums. Specifically, citizens who favour the policy proposal or believe that they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…Another example of how the literature on public support for referendums may feed into studies on citizens’ populist attitudes and referendums are insights from recent studies on instrumental motivations for support for direct democracy (Werner 2020). Public support for referendums is not only driven by ideological attitudes (like populist attitudes).…”
Section: A Problem Of Theoretical Framing: Citizens’ Preferences About Who Should Governmentioning
confidence: 99%
“…Another example of how the literature on public support for referendums may feed into studies on citizens’ populist attitudes and referendums are insights from recent studies on instrumental motivations for support for direct democracy (Werner 2020). Public support for referendums is not only driven by ideological attitudes (like populist attitudes).…”
Section: A Problem Of Theoretical Framing: Citizens’ Preferences About Who Should Governmentioning
confidence: 99%
“…How distrustful populists react to opinion changes in minipublics is an open (empirical) question. An experiment on preferences for direct democracy in Belgium shows that distrustful populists may have strategic considerations when choosing democratic innovations; they hope that their substantive policy preferences might win a majority in the context of such alternative procedures (Werner 2019). Hence, if they see minipublics merely as a strategic means to implement their preferred goals (on their account ' corrupted' by legacy institutions), then the legitimacy of minipublic recommendations will wither away quite quickly when a minipublic decides against their own preferences.…”
Section: Taking the Heterogeneity Of Citizen Preferences Seriouslymentioning
confidence: 99%
“…We controlled for this using a basic measure of political interest (0 = 'not at all interested'; 10 = 'very interested'; M = 6.0; SD = 3.0). Previous research has found that anticipation of a particular outcome and thinking that you are in the majority are significant drivers of support for referendums (Werner 2020). Therefore, we controlled for majority perceptions by asking respondents to state their level of agreement with the following statement on a five-point Likert scale: 'The views that I have are generally shared by the people of Northern Ireland' (1 = 'totally disagree'; 5 = 'totally agree'; M = 3.2; SD = 1.0).…”
Section: Survey Designmentioning
confidence: 99%